PENGARUH SIKAP KEUANGAN, PENDAPATAN, DAN GENDER TERHADAP PENGELOLAAN KEUANGAN KELUARGA - Ramadhani, Mardiatul; Rissi, Dita Maretha; Sriyunianti, Fera (Journal of Applied Accounting And Business, 2023)
This study aims to determine and analyze the effect of financial attitudes, income and gender in family financial management. This study is a type of quantitative. The data used in this study is primary data with a data collection method using questionnaire sheets distributed to respondents. The population of this study is people who live in South Nagari Kajai West Pasaman.  The sample in this study was 150 respondents. The sampling technique in this study is convenience sampling. The analysis method in this study uses multiple linear regression analysis using the SPSS version 25 application. The results of this study show that partial  financial attitudes, income and gender have a significant effect in family financial management in Nagari Kajai Selatan, West Pasaman.  Simultaneously that financial attitudes, income and gender together have effect in family financial management in South Nagari Kajai West Pasaman.